2022
DOI: 10.1515/tlr-2022-2097
|View full text |Cite
|
Sign up to set email alerts
|

An experimental perspective on embedded gapping in Persian

Abstract: This paper empirically tests the embedding constraints on gapping in Persian. It has been suggested that gapping differs from other kinds of ellipsis in banning embedding. However, the first counter-examples in the literature come from Persian. Following up on previous experiments on embedded gapping in several languages, we report the results of two acceptability judgment tasks. Our results show that, while embedded gapping is overall acceptable in Persian, speakers’ acceptability judgements also vary dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…(52) […] we want to treat your POWs [prisoners of war] with dignity and we hope that you do ours as well. (COCA, spoken, 2008-) Third, languages may differ with respect to the preference between an elliptical construction and its non-elliptical counterpart: our experimental results from English show that, without embedding, there is a general preference for non-gapping constructions in English (as observed by Carlson 2001); on the other hand, no clear preference for either gapping or non-gapping construction was attested in Romance languages (Bîlbîie et al 2021), whereas in Persian, a clear general preference for gapping was observed (Bîlbîie & Faghiri 2022). The fact that gapping has a very low frequency in language use in English (Tao & Meyer 2006) could be related to this ellipsis penalty in this language.…”
Section: Towards a Construction-based Fragment Analysismentioning
confidence: 62%
See 4 more Smart Citations
“…(52) […] we want to treat your POWs [prisoners of war] with dignity and we hope that you do ours as well. (COCA, spoken, 2008-) Third, languages may differ with respect to the preference between an elliptical construction and its non-elliptical counterpart: our experimental results from English show that, without embedding, there is a general preference for non-gapping constructions in English (as observed by Carlson 2001); on the other hand, no clear preference for either gapping or non-gapping construction was attested in Romance languages (Bîlbîie et al 2021), whereas in Persian, a clear general preference for gapping was observed (Bîlbîie & Faghiri 2022). The fact that gapping has a very low frequency in language use in English (Tao & Meyer 2006) could be related to this ellipsis penalty in this language.…”
Section: Towards a Construction-based Fragment Analysismentioning
confidence: 62%
“…If the true factive predicate penalty comes from the fact that the gapped clause must address the same QUD as the antecedent clause, we expect it to be universal. Recent experimental work (also based on several acceptability judgments tasks) by Bîlbîie & de la Fuente (2019) for Spanish, Bîlbîie et al (2021) for Romanian and Bîlbîie & Faghiri (2022) for Persian show that embedded gapping is possible in these languages, and that non-factive verbs embed more easily than factive ones; and among factive verbs, semi-factive (e.g. cognitive) predicates embed more easily than true factive (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations